2022
DOI: 10.3390/su14063342
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Issues in Research on Biodiversity Conservation and Tourism Sustainability

Abstract: The rationale of this article is the need to elicit the trending themes relevant to the latest research on biodiversity conservation and tourism sustainability. Hence, the purpose of this study: stocktaking of cutting-edge research articles in this field and eliciting the critical trends and issues shaping the knowledge, future research, and technical development perspectives on biodiversity conservation and tourism sustainability. The focus is on the trends, which are pivotal for achieving the UN Sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…In reviewing 'Current Trends and Issues in Research on Biodiversity Conservation and Tourism Sustainability', Jurkus et al (2022) identified seven 'trending research themes on biodiversity conservation and tourism sustainability', namely community-based tourism, national park management, sustainable tourist motivation, biodiversity conservation and ecotourism, landscape and land use changes, visitor satisfaction monitoring, and ecotourism modelling. More specifically, Jurkus et al (2022) argued that 'a current critical strand of research on biodiversity conservation and tourism sustainability deals with transformations of the strict top-down, prescriptive approach, particularly in countries with strong traditions of centralized planning.' Further Jurkus et al (2022) suggested that 'in many countries with top-down biodiversity conservation, nature-based tourism is often developed by larger tourism companies', and that such companies 'are more advantageous regarding lobbying and bending the conservation restrictions but ignore local socio-economic conditions.…”
Section: Project and Policy Reports And Academic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In reviewing 'Current Trends and Issues in Research on Biodiversity Conservation and Tourism Sustainability', Jurkus et al (2022) identified seven 'trending research themes on biodiversity conservation and tourism sustainability', namely community-based tourism, national park management, sustainable tourist motivation, biodiversity conservation and ecotourism, landscape and land use changes, visitor satisfaction monitoring, and ecotourism modelling. More specifically, Jurkus et al (2022) argued that 'a current critical strand of research on biodiversity conservation and tourism sustainability deals with transformations of the strict top-down, prescriptive approach, particularly in countries with strong traditions of centralized planning.' Further Jurkus et al (2022) suggested that 'in many countries with top-down biodiversity conservation, nature-based tourism is often developed by larger tourism companies', and that such companies 'are more advantageous regarding lobbying and bending the conservation restrictions but ignore local socio-economic conditions.…”
Section: Project and Policy Reports And Academic Literature Reviewmentioning
confidence: 99%
“…More specifically, Jurkus et al (2022) argued that 'a current critical strand of research on biodiversity conservation and tourism sustainability deals with transformations of the strict top-down, prescriptive approach, particularly in countries with strong traditions of centralized planning.' Further Jurkus et al (2022) suggested that 'in many countries with top-down biodiversity conservation, nature-based tourism is often developed by larger tourism companies', and that such companies 'are more advantageous regarding lobbying and bending the conservation restrictions but ignore local socio-economic conditions. '…”
Section: Project and Policy Reports And Academic Literature Reviewmentioning
confidence: 99%
“…Tourism has experienced dynamic development in recent decades and has become one of the fastest growing industries (Jurkus et al, 2022;UNWTO, 2022a); however, in 2020 and 2021 there was a significant halt in the growth trend in connection with the spread of COVID-19 and the travel restrictions of various countries, (Anguera-Torrell et al, 2021;Harchandani and Shome, 2021;Lagos, Poulaki, Lambrou, 2021). During these two years, tourism experienced unprecedented changes that had an impact on the economic stability of a number of countries (Duro et al, 2021;Zhong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An eco-tourism site that is developed using conventional mass tourism may harm the tourism destination (Mondino and Beery, 2019;Rybchenko et al, 2022). Ecotourism is a tourism development approach aiming for conservation and sustainable development (Baloch et al, 2022;Jamaliah and Powell, 2018;Jurkus et al, 2022). Essentially, eco-tourist's purpose is to preserve the environment, maintain society's well-being, and teach tourists (Bricker, 2017).…”
Section: Introductionmentioning
confidence: 99%